Controlling coefficients of thermal expansion in thermoplastic materials: effects of zinc cyanide and ionic liquid. Issue 10 (20th April 2022) - Egerton, Savannah; Sim, Claudia; Park, Heon E.; Staiger, Mark P.; Patil, Komal M.; Cowan, Matthew G.
Abstract : Tuning the coefficients of thermal expansion (CTE) of polymeric materials through a combination of zinc cyanide and ionic liquid. Abstract : Tuning the coefficients of thermal expansion (CTE) of materials is necessary to control performance and extend the operational life of precision equipment. Herein, we report the strategy of creating 3-component composite materials from the thermoplastic poly(ethylene), zinc cyanide as a solid with a negative coefficient of thermal expansion (NTE), and ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM][TFSI]) as an interfacial agent that enhances the polymer/solid interface. Specifically, we produce thermoplastic composites with coefficients of thermal expansion reduced from 290 to 190 × 10 −6 K −1, a significantly larger reduction than the ca. −15 × 10 −6 K −1 reported for composites containing other NTE fillers. Additionally, the composite materials retain a Young's modulus comparable to low density polyethylene (80–110 MPa). Overall, this three-component design strategy shows promise for the development of thermoplastic materials with controlled coefficients of thermal expansion.